AVAXX101x: assessing the first edX course on antivaccination and vaccine hesitancy - Aechtner, Thomas (Frontiers in Education, 2025)
Vaccine hesitancy remains a significant global health challenge, yet accessible, systematic courses addressing this issue have been scarce. To fill this gap, the University of Queensland developed and launched “AVAXX101x: Antivaccination and Vaccine Hesitancy” on the edX platform in 2021. This was the world’s first edX MOOC focused on countering antivaccination claims and addressing vaccine hesitancy. The course aimed to educate healthcare workers, public health professionals, and the general public, offering evidence-based strategies to address vaccination doubts. This paper discusses the course’s objectives, content, design, and descriptively examines student demographics and survey responses, along with learner feedback. Findings reveal that AVAXX101x attracted a diverse cohort from 144 countries, including significant representation from UN-identified developing economies and a higher-than-average proportion of female learners. The course achieved respectable completion rates and garnered overwhelmingly positive feedback. Cumulatively, AVAXX101x successfully met its objectives by enhancing students’ understanding of vaccines, vaccine safety, and vaccine hesitancy. It further demonstrates how open online courses can be effective tools to equip learners with strategies for addressing vaccine hesitancy, as well as an educational means to sway vaccine hesitant participants.